Technical Writing at LBCC - Will Fleming (Linn-Benton Community College, 2020)
An open textbook that gives students an overview of the kinds of writing they’ll be expected to do in upper-level college courses, the workplace, and beyond. The book covers the main elements of technical communication and provides students opportunities to put those elements into practice. It explores how writers locate, create, and deliver technical information. This course and this textbook will provide you instruction and practice in writing documents commonly used in the workplace, such as emails, memos, and letters, as well as employment documents, such as resumes and cover letters. You will also learn about writing descriptions, summaries, instructions, proposals, and various technical reports. You will learn about the importance of audience and purpose in technical communication and how to choose a format and style appropriate for your specific audience and purpose. You will also have an opportunity to work collaboratively with your classmates.